Effect of mixing on performance of finishing swine - Hines, Robert H. (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service, 2010)
Two feeding trials were conducted to evaluate the effect of mixing finishing pigs on subsequent performance. Growth rate of heavier pigs was reduced 15-35% in the two weeks after mixing when compared to the non-mixed pigs. This reduction in weight gain resulted in a significant difference in average daily gain overall for pigs mixed at 5 weeks compared to non-mixed pigs. An 8% reduction in the two weeks following mixing was observed for pigs mixed at 3 weeks compared to non-mixed pigs. However, during the following weeks of the trial, these pigs recovered, resulting in a non-significant reduction overall in average daily gain. In trial 2, pigs that were sorted randomly into two groups at 5 weeks grew 6% faster than controls and overall had a significantly faster rate of gain than controls.
Keywords: Swine; Performance; Finishing pigs